A oferta de serviços ambientais na bacia hidrográfica dos rios Sorocaba e Médio Tietê - Kawaichi, Vanessa Mayumi (Universidade Federal de São Carlos, 2012)
The present study aims to estimate the supply of environmental services Sorocaba Rivers Basin and Middle Tietê, located in the central-southeastern state of Sao Paulo. The focus of the environmental service is given to the hydrological services, which are responsible for providing farmers in the region. Thus, from the provision of environmental services in the Basin, we estimated the value of PES to farmers based on the opportunity cost of changing agricultural practices on farms in the region. The methodology is based on the opportunity cost of changing a conventional practice for a conservation practice. The opportunity cost was obtained from the comparison between the yield of each crop analyzed by adopting the conventional practice and practice conservation. Thus, we analyzed the yields of major crops Basin (coffee, corn, beans, potatoes, sugar cane, orange, tomato, onion, grapes, rice and cassava), comparing the difference between the yields for both practices. The classification for conservation practice and conventional practice followed at the discretion of the forest area of the basin, considering the municipalities with an area of forest above average as conservation and below average, as conventional. Thus, the forest area was used as a proxy for measuring the environmental service in question, knowing that the preservation of vegetation provides a number of benefits, including conservation of water resources. The results show that the estimated values of PES for the main crops of the Basin can range from R$100/ha/year to R$30.000/ha/year. In relation to the cultures analyzed in this study, we can say that with the highest potential for implementation of programs for PES were the crops of rice and cassava, which, besides having more profitable return for the conservation practice, have a initial offering of high environmental services and the lowest values for PES. Cultures orange, tomato, onions and grape also have an initial supply of high environmental services, however, PES values are estimated quite high in comparison with other cultures, thereby implementing programs to increase the supply PES environmental services in this case should consider how much the payment would compensate for the provision of environmental services provided by these cultures.
Keywords: recursos hídricos valoração ambiental; recursos hídricos serviço ambiental; produtor rural pagamento por serviços ambientais (PSA); instrumentos de incentivo; microbacia; recursos hídricos.; incentive instruments; PES; watershed; water resources; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS::ECONOMIA DOS RECURSOS NATURAIS